Electrodeposition and corrosion behaviour of nanostructured cobalt–tungsten alloys coatings. (1st November 2016) - Vernickaite, E.; Tsyntsaru, N.; Cesiulis, H.
Abstract : Theoretical and practical studies of tungsten alloys with iron group metals continue to be carried out because of their unique combination of tribological, magnetic and electrical properties. The electrodeposition of Co–W alloys was performed in a citrate–borate solution at pH 5–8; t  = 20 and 60°C. The electrochemical corrosion was studied in 0.01 M H2 SO4, and stainless steel was selected as a substrate. For the mapping of the properties alloy deposits having various contents of W (2.4–30 at.-%) and crystallite size varying from polycrystalline (<60 nm) to 'amorphous-like' (2–5 nm) were prepared. Co–W alloys possessing the highest corrosion resistance should contain 17–24 at.-% of W, i.e. have a structure close to intermetallic phase Co3 W. The corrosion occurs via an intermediate adsorbed stage by forming oxygen-containing compounds; the estimated thickness of the adsorbed layer varies in the range 0–1.6 Å.